2018
DOI: 10.1016/j.ecosys.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Intraday effect of news on emerging European forex markets: An event study analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
3
11
0
Order By: Relevance
“…Finally, the empirical results show that there is no leverage effect in the all examined financial time series. The above results of three new EU currencies are consistent with Kočenda and Moravcová (2016) who find, that the longest reaction in terms of significant abnormal returns after the German/Eurozone news release can be traced to the announcements of the PMI indices, Retail Sales, the IFO and Industrial Production. The data show that ECB meeting days do not influence new EU exchange rate volatility during 2010-2015.…”
Section: Resultssupporting
confidence: 89%
“…Finally, the empirical results show that there is no leverage effect in the all examined financial time series. The above results of three new EU currencies are consistent with Kočenda and Moravcová (2016) who find, that the longest reaction in terms of significant abnormal returns after the German/Eurozone news release can be traced to the announcements of the PMI indices, Retail Sales, the IFO and Industrial Production. The data show that ECB meeting days do not influence new EU exchange rate volatility during 2010-2015.…”
Section: Resultssupporting
confidence: 89%
“…Abnormal returns can be the result of herd effects (Griffin and Tversky 1992;Madura and Richie 2004), the behavior of "noise" traders (Aiyagari and Gertler 1999;Hong and Stein 1999), different cognitive traps and biases such as overconfidence and other behavioral patterns (Barberis et al 1998;Daniel et al 1998), low liquidity (Jegadeesh and Titman 1993), macroeconomic announcements (Kocenda and Moravcová 2018), and the use of technical analysis for making investment decisions (Duran and Caginalp 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There were found significant relation, which shows that more freedom of the press and lower level of stock price synchronicity, enhancing information conditions of stock markets [26]. Another study in the field of stockiest prices suggested that free press enables free market disclosure with a more rapid market reaction [27]- [28], while media censorship affects foreign share discounts and international capital flows [29]. On the entity level, countries with freer media have more chances that corporate social responsibility activity enhances the value of local firms [30] as well as is considered a business environment and obstacles less significant [31].…”
Section: Review Of Literaturementioning
confidence: 93%